Cultivating Ethical and Politically Rooted Research Practices With Undocumented Migrants - León, Lucia (2024)
One of the authors and two co‐editors of the anthology We Are Not Dreamers: Undocumented Scholars Theorize Undocumented Life in the United States reflect on the meanings, emotions, and expectations of the project as they are associated with the factor of time. While academic timelines can feel urgent and pressing, the authors learned through their collective work that when guided by a politics of care, the slowing of time can be a foundation for an ethical and political imperative in research with undocumented immigrants and scholars. Researchers with a deep commitment to the community they write about can rely on time to digest information slowly and to handle complex emotions as they theorize difficult experiences that may parallel their own lives. Time can also be prioritized to grant study participants multiple rounds of feedback for each written piece, until they feel comfortable with how their experiences are represented. We also reflect on the need for researchers to take their time in developing an ethical data collection process. For example, conducting interviews with care with undocumented migrants requires researchers to take the time to get to know people, give them time to reflect during the conversation, and consider the timing of questions to ensure that each interview minimizes harm to interviewees. In these ways, we highlight the importance of extending time as an ethical imperative of doing research with undocumented migrants.